گۆران و هێریک لێکۆڵینەوەیەکى بەراوردکارییە لە نێوان دوو هۆنراوەیاندا: "بۆ گوڵى لاولاو" و "بۆ گوڵەنێرگزەکان" - الدین, گەلاوێژ ئیبراهیم محى (Sulaimani Journal for Humanities, 2003)
In literature, as in any other field of knowledge , writers and innovators usually make use of the works and productions of those who preceded them and also their contemporaries. This can be done as a means to achieve new works or productions in order to continue what others had begun on the way of building the huge human civilization. Following the same principle, the great kurdish poet, Abdulla Goran came under the influence of foreign literature , especially English literature and poetry. In my research I proved that this influence was something natural , healthy, and very useful to him .It is well justified because it enriched his educational and cultural background. He did not use the new education which came from foreigners uselessly as a mere imitator , but on the contrary, he moulded it again as a thinker and genius, in order to make it acceptable to the kurdish culture and taste. It was changed in a way that makes it new and remarkable in serving the kurdish society.